USE OF COLOURS IN POST-MODERNIST INDIAN CREATIVE ADVERTISEMENTS - Saha, Ali (International Journal of Research -GRANTHAALAYAH, 2014)
Post Modernism in India is believed to have evolved after Indian Independence in 1947 and continues till the early 20’s. When we talk about Post Modernism in context to India, it is often connected to the country’s modernization and decolonization. After the Indian independence, advertising developed with the development of forms of media at each decade. Since the beginning, colours have stirred our emotions. White chalk was a precious tool in the hands of Palaeolithic artists. Gold from the very first civilisations reminded us of the sun. A desire for the mysterious and exotic blue changed the course of history. Colour was definitely grabbing worldwide attention as the civilizations advanced, but it certainly wasn’t easy to get hold of. This is why it became the ultimate symbol of luxury. Those who could afford it, used favourite hues to decorate their surroundings. Today, not so long since the beginning of the Digital Revolution, we have free access to any colour we can possibly think of, and more and we use it in abundance and variances in Indian Advertising, basically since 1950’s when colour ads occupied special importance amongst the people who were only confined to black and white images and ads. Colour is powerful because it can change our mood – the mood of potential customers. Advertisers and designers are well aware of, the fact that customers are not guided entirely by logic when making purchases, but tend to be driven by less identifiable factors such as emotions. Through colours we can control reactions of an audience and provoke them to certain behaviours. Creativity in one word can be described as being different, i.e. different from the quo. The designer’s role is to build clear and understandable communication through the impact of colour. Creative advertisers use more dramatic mixture of colours in those ads to differentiate them from the general clutter of the ads and also to produce stronger communicative effect. The following paper presents examples of ads from mid 1990’s till the onset of 21t century and description of its colours. This paper will also present the aesthetics related to those colours and their suitability in designing those ads, to attract maximum consumers by appealing their senses.